Evaluation of Federal Road Safety Commission Public Enlightenment Programme in South-West, Nigeria (2012)
The Federal Road Safety Commission was established to curtail the high rates of accident and loss of lives on Nigerian roads. The commission aimed at educating road users on road safety. However, studies show that the rates at which accidents happen on roads are still seemingly high. Thus, the study evaluated the FRSC public education (PE) programme to determine its effectiveness in fostering road safety consciousness in the drivers. The study also investigated road users‟ perception of the effectiveness of the PE programme and the concomitant constraints. The study adapted an ex post facto design, using Stake‟s Countenance of Educational Evaluation (also known as Antecedent, Transaction and Outcome) as the evaluation model. Simple random sampling technique was used to select six local government areas namely: Oshodi/Isolo, Amuwo odofin, Ikeja, and Ibadan North, Ibadan North East and Oluyole of Lagos and Oyo states respectively. A total of 510 drivers, 420 commuters and 100 FRSC staff were selected using multi stage, purposive and simple random sampling techniques. Five validated instruments were used to collect data: Drivers‟ Perception of FRSC Public Enlightenment Programme Questionnaire (r=0.82), Commuters‟ Perception of FRSC Public Enlightenment Programme Questionnaire (r=0.75), FRSC Staff Perception of the Programme Questionnaire (r=0.77), Drivers‟ Observance of Road Traffic Rules and Regulations Checklist (r=0.78) and Knowledge of Highway Traffic Code Assessment Test (r=0.82). Eight research questions guided the study. Data were analysed using, Percentages, Pearson Product Moment Correlation, t-test and ANOVA at 0.05 level of significance. The results showed that only 32.5% of the sampled drivers have high knowledge of the Highway Code (Lagos 34.14%, Oyo 31%) and there is no significant difference in the level of knowledge of drivers from the two states (t=1.51,df 498, p>0.05). Sampled drivers and commuters indicated that FRSC public enlightenment programme has brought significant improvement to road traffic situation (t =41.38, df 919, p<0.05) while 67% of the Commission‟s staff indicated that inadequate fund and equipments among others, are constraints hindering proper achievement of the programme‟s objectives. Drivers who attended driving schools differ significantly in their knowledge of the Highway Code compared to those who did not (t =25.58, df 498, p<0.05). Drivers who attended driving schools have higher knowledge. There was also correlation between commercial drivers‟ level of knowledge of Highway Code and their behaviour on the road (r=0.19; p<0.05). Drivers differ significantly in their knowledge of the Highway Code by type {commercial, hired private and private owner drivers} (F (2,497) =52.95p<0.05).Private owner drivers have the highest knowledge followed by the private hired drivers. FRSC Public Enlightenment Programme objectives have not been effectively achieved. Some acts of indiscipline such as reckless driving, over speeding are still very common on the road. Drivers have little knowledge of road signs. Thus, more intensive enlightenment campaigns should be carried out, the programme should be adequately funded, necessary equipment should be provided and drivers should be regularly retrained. Model driving schools should also be established for training and retraining of drivers before issuance and renewal of driving licences respectively